Immediate Effect Of Surface Laryngeal Hydration Associated With Tongue Trill Technique In Amateur Singers - Pereira, Maria Cecilia Bayer [UNESP]; Onofri, Suely Mayumi Motonaga [UNESP]; Spazzapan, Evelyn Alves [UNESP]; da Silva Carrer, Joyra [UNESP]; da Silva, Luana Alves [UNESP]; Fabbron, Eliana Maria Gradim [UNESP] (FapUNIFESP (SciELO), 2021)
Purpose: To analyze the immediate effect of laryngeal surface hydration associated with the performance of Tongue Trills (TT) on singers. Methods: Thirty singers without vocal complaints or laryngeal alterations divided into control (CG) and experimental (EG) groups. The CG performed the TT for five minutes. The EG was submitted a nebulization with 3 ml of saline solution followed by TT for five minutes. Voice self-assessment, acoustic analysis and perceptual assessment were performed at Pre (Pre TT) and post (PTT) moments in CG and pre (Pre TT), post hydration (PH) and post hydration + TT (PHTT) in GE. In the self-assessment were evaluated quality, stability, vocal intensity and hoarseness. There were extract the values of the Fundamental frequency; Jitter%; Shimmer%, Noise-to-harmonic Ratio e Cepstral Peak Prominence-Smoothed CPPs in the acoustic analyze. The perceptual evaluation was performed by an experienced speech therapist. Results: Comparing the results of self-assessment between groups showed improvement in the perception of stability and vocal intensity in the PTT (CG) in relation to PH (EG). Comparison between the EG moments showed a statistical difference in the vocal intensity perception, indicating a better results for PHTT. There was no statistical difference between the groups investigated in the perceptual assessments and acoustic analysis. Conclusion: Surface laryngeal hydration does not potentiate the effect of TT on naturally hydrated singers with 3ml nebulization. For voice professionals with high vocal demand, surface hydration can be introduced during voice use to maintain vocal quality.
Efeito imediato da hidratação laríngea de superfície associada à técnica de vibração sonorizada de língua em cantores amadores
Keywords: Adults; Hydration; Voice; Voice Quality; Voice Training